Students with Self-identified Special Educational Needs and Disabilities (si-SEND): Flourishing or Languishing!. Issue 1 (2nd January 2016) - Skrzypiec, Grace; Askell-Williams, Helen; Slee, Phillip; Rudzinski, Adrian
Abstract : Students' wellbeing is an essential component of their ability to function well, not only at school but also in all life domains. Many studies have investigated student wellbeing. However, empirical studies about the wellbeing of students with special educational needs and disabilities (SEND) are scarce. Furthermore, many studies have adopted a deficit view of wellbeing and mental [ill]-health. This study adopted a more positive perspective. We administered a questionnaire assessing social-emotional and psychological wellbeing, global self-concept, resilience, bullying, mental ill-health and school satisfaction to 1930 students, aged 13–15 years, who were attending seven mainstream schools in South Australia. Of those students, 172 self-identified as having SEND. Results showed significant differences, with students who self-identified with SEND not faring as well as other students on all measures. In particular, just over one third (39.9%) of students who self-identified as having SEND reported that they were flourishing, compared with just over half (57.6%) of the students who did not indicate that they had special needs. The findings indicate that more attention needs to be given to designing and implementing supports to improve the wellbeing and school satisfaction of students who self-identify as having SEND.